PRELIMINARY PHYTOCHEMICAL SCREENING AND HPTLC FINGERPRINT PROFILE OF LEAF EXTRACTS OF HOLOPTELEA INTEGRIFOLIA (ROXB.) PLANCH - SUTAR, RAVINDRA C; KASTURE, SANJAY B; VK, KALAICHELVAN (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The objective was to develop the fingerprint profile of medicinally and economically useful leaves of Holoptelea integrifolia (Roxb). Planch using high-performance thin layer chromatography (HPTLC) technique. Materials and Methods: Preliminary phytochemical screening was done, and HPTLC studies were carried out. Camag HPTLC system equipped with Linomat V applicator (Switzerland). Densitometric scanning was performed with Camag TLC Scanner IV in the reflectance absorbance mode at 540 nm and operated by Win CATS software (1.4.6 Camag) with the help of Tungstant lamp. Results: Preliminary phytochemical screening of petroleum extract of H. integrifolia showed the presence of steroids, terpenoids, alkaloids, glycosides, flavonoids, proteins, tannins and carbohydrates, whereas methanolic extract of H. integrifolia showed the presence of steroids, alkaloids, flavonoids, proteins and carbohydrates. HPTLC fingerprinting of petroleum ether extract of leaf revealed 9 polyvalent phytoconstituents (9 peaks) and corresponding ascending order of Rf values in the range of 0.44-0.81. While methanol extract of leaf showed 10 polyvalent phytoconstituents (10 peaks) and corresponding ascending order of Rf values in the range of 0.18-0.80. Conclusions: It can be concluded that HPTLC fingerprint analysis of leaf extract of H. integrifolia (Roxb) Planch can be used as a diagnostic tool for the correct identification and authentication of the plant and it is useful as a phytochemical marker and also a good estimator of genetic variability in plant populations. Keywords: Holoptelea integrifolia (Roxb) Planch leaf, Phytochemical screening, High-performance thin layer chromatography fingerprinting.